Food-specific IgG-based elimination diet decreased IL-6, TNF-α, and CGRP and improved symptoms in adults with migraine - Zhao, Zhiming; Yang, Meimei; Wan, Fujun; Ning, Baoli; Song, Tao; Fu, Jun; Zhang, Liming (Frontiers in Nutrition, 2025)
BackgroundFood-specific IgG antibodies have been proposed to be biomarkers to identify food that triggers an inflammation response. We aimed to evaluate the effect of a food-specific IgG-based elimination diet by assessing the changes in the symptoms of migraine and its comorbidities, inflammatory cytokines, neuropeptides, and neurotransmitters, and their correlation.MethodsThis was a sham-controlled randomized trial. A total of 98 patients with migraine who had at least one positive food-specific IgG antibody were randomly assigned to either the true diet group (IgG-positive foods were excluded, n = 52) or the sham diet group (alternative IgG-negative foods were excluded, n = 46). At baseline and at the end of 12 weeks, seven questionnaires were administered regarding the symptoms of migraine, gastrointestinal symptoms, anxiety, depression, and sleep quality. Fourteen food-specific IgG antibodies, such as IL-6, IL-10, TNF-α, 5-HT, calcitonin gene-related peptide (CGRP), and vasoactive intestinal peptide (VIP), in serum were assessed using enzyme-linked immunosorbent assays.ResultsAt the end of 12 weeks, the true diet group had a larger reduction in questionnaires of migraine (except for MSQ), gastrointestinal symptoms, and poor sleeping, as well as food-specific positive IgG, IL-6, TNF-α, and CGRP in the serum. The difference in the change of “days with migraine in past 4 weeks” between the sham and true diet groups was significantly attenuated after adjusting for IL-6 and TNF-α.ConclusionAn IgG-positive food elimination diet improved migraine and its comorbidities and reduced IL-6, TNF-α, and CGRP, which might be associated with the alleviated systemic chronic inflammation and downregulation of the sensitivity of trigeminal nerve endings.Clinical trial registrationChictr.org.cn, identifier ChiCTR2000039278.